Determination of mechanical properties of Al2O3/Y-TZP ceramic composites: Influence of testing method and residual stresses. Issue 16 (December 2016) - Fan, Kunyang; Pastor, Jose Ygnacio; Ruiz-Hervias, Jesus; Gurauskis, Jonas; Baudin, Carmen
Abstract: A series of Al2 O3 /Y2 O3 -stabilized zirconia (Y-TZP) ceramic composites with different zirconia contents (5 and 40 vol% Y-TZP) and fabricated by different green processing techniques (a novel tape casting and conventional slip casting) were studied. The microstructure and mechanical properties of the composites were investigated systematically, by means of scanning electron microscopy, Vickers indentation, depth-sensing nanoindentation, and single-edge laser-notched beam (SELNB) techniques. The indentation fracture method was found to be unsuitable for fracture toughness determination in this work. Reliable values of fracture toughness were obtained by the SELNB method with an almost atomically sharp laser-machined initial notch. The microstructure and mechanical properties of the ceramic composites mainly depended on the Y-TZP content. No significant differences were induced by the choice of green processing technique. The contribution of residual stresses to fracture toughness in Al2 O3 /Y-TZP ceramic composites was investigated. To this end, a theoretical model was applied to estimate the increase in fracture toughness due to the measured residual stresses in the samples. It was found that in this case, residual stresses were not the main factor responsible for the toughening in Al2 O3 /Y-TZP composites.